Analisis Pengaruh Logat Bahasa Batak Toba yang Mempengaruhi Komunikasi Bahasa Indonesia : Studi pada Mahasiswa Asal Samosir - Bima Pandawa Sinurat; Desi Marlina Sidabutar; Edoward Fran Silalahi; Ramona Febiola Simorangkir; Nurul Azizah (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
This research aims to analyze the influence of the Batak Toba language accent which influences Indonesian language communication among students from Samosir. This research uses a qualitative descriptive research method, with a survey research type. The results of this research discuss the obstacles of students from the Samosir area in adapting Toba Batak language to Indonesian language communication in various situations. This research also discusses the influence of the Toba Batak accent in the academic sphere of students from Samosir and provides strategies for adapting the Toba Batak accent so that Indonesian language communication is more effective. The use of Toba Batak accent in Indonesian language communication can have different impacts depending on the context faced by students. This accent can also be an obstacle in communication, especially if it is not well understood by the person you are talking to. Therefore, This research shows that the strategies used to adapt the Batak Toba accent in Indonesian language communication also vary. Thus, it is important to understand the good and correct use of the Indonesian language, as well as respecting the diversity of languages and cultures that exist in Indonesia, so that it can strengthen national togetherness and unity.